Dietary preferences for food items among children of age 5-10 years in a rural area of Perambalur district, South India - Kulothungan, Karthikeyan; Sri Ranganathan, T.; Rock Britto, D.; Deepak, S. G.; Dhinesh, K.; Dhinesh Raj, M.; Farhana, Fathima; Ganesh, P.; Gayathri, D. (International Journal Of Community Medicine And Public Health, 2018)
Background: Appropriate nutrition in early childhood plays an important role in normal growth and development, as well as on the long-term health of individuals. There is increasing recognition that dietary pattern better reflects the overall quality of the diet. The dietary pattern has been shown to be associated with nutrient intakes and linked to chronic diseases including obesity, diabetes and metabolic syndrome in children. The aim of the study was to assess the dietary preferences for food items (vegetables, fruits, meat, milk products, snacks and starch) among children of age 5-10 years in the rural area of Perambalur district, South India. Methods: Six food categories (vegetables, fruits, meat, milk products, snacks and starch) were included in the questionnaire to study the dietary preferences of the child. Data were entered into a Microsoft Excel worksheet and analysed for frequencies and percentages. Mean score and its standard deviation were calculated for individual food items. Results: The study shows that most of the children prefer milk/milk products with a highest mean score of 3.94 followed by a preference for snacks. Most avoided food were vegetables, followed by meat and meat products. The overall score was found to be low for all the categories of food among children who prefer mobile compared to TV and outdoor group. But this difference was not statistically significant. This difference was close to 0.05 only in vegetable group category. Conclusions: The results will help in planning the nutritional counselling programmes for children. These findings have to be further correlated with the nutritional status of the individual children and deficiencies if any.